Balancing between caregiving and professionalism—Women's narratives on fostering a victim of maternal sexual abuse. Issue 4 (20th July 2018) - Wubs, Dorijn; Batstra, Laura; Grietens, Hans
Abstract: The impact of sexual abuse on children is enormous, particularly when a child is abused sexually by a mother figure. In order to gain insight into the experiences of this rarely studied group, the life stories of four foster mothers of victims of maternal sexual abuse were collected. The narratives were coded inductively, and several topics concerning foster motherhood were studied more in‐depth. Four key themes emerged in the women's narratives: their attitude towards the abusing female, the foster child's sexual behaviour towards the foster mother, the emotional and physical distance of the foster mothers towards their foster child, and lastly, their sense of responsibility. The four foster mothers continuously balance between fostering their foster child as a parent and responding as a professional caregiver. The consequences of being a foster mother of a victim of maternal sexual abuse should be more socially acknowledged.